Free Chlorine Concentration Decay Rate with Fast and Slow Reacting Agents Along with Service Age of the Distribution System - Rakesh Chandra Bhadula; Ganesh Prasad Pokhariyal; Chandan Singh Ujarari (International Journal of Mathematical, Engineering and Management Sciences)
One of the most crucial elements influencing the rate of chlorine decay in drinking water networks is the service age of pipes of the distribution system, which has been introduced in this study. The aim of the study was to demonstrate the effect of the distribution network's service age and the chlorine degradation rates with the concentration of slow- and fast-reacting agents which were investigated under the fixed temperature of 30 degrees centigrade and the results are displayed with the help of various graphs. It was found that with ageing factor of 0.01 chlorine concentration took 16 hours to become zero while on the other hand with ageing factor of 0.4 the chlorine concentration reduced to zero in 8 hours. Through correlation analysis a very strong positive correlation was found to be 0.9830450 with ageing factor of 0.1 for newly built pipeline on the other hand it was found to be slightly lower with the value 0.978139 with ageing factor of 0.4 for old pipeline.